The prevalence of concurrently raised blood glucose and blood pressure in India: a cross-sectional study of 2035 662 adults - Bischops, Anne Christine; Manne-Goehler, Jennifer; Jaacks, Lindsay; Awasthi, Ashish; Theilmann, Michaela; Davies, Justine; Atun, Rifat; Bärnighausen, Till; Vollmer, Sebastian; Geldsetzer, Pascal (Journal of hypertension, 2019)
Objective: To inform integrated, person-centered interventions, this study aimed to determine the prevalence of having both a raised blood glucose and blood pressure (BP) in India, and its variation among states and population groups. Methods: We pooled data from three large household surveys (the Annual Health Survey, District Level Household and Facility Survey, and National Family Health Survey), which were carried out between 2012 and 2016 and included adults aged at least 15 years. Raised blood glucose was defined as having a plasma glucose reading at least 126mg/dl if fasted and at least 200mg/dl if not fasted, and raised BP as a SBP of at least 140mmHg or DBP of at least 90mmHg. The prevalence of having a concurrently raised blood glucose and BP (comorbid) was age-standardized to India's national population structure, and disaggregated by sex, age group, BMI group, rural-urban residency, household wealth quintile, education, state, and region. RESULTS: The age-standardized prevalence of this comorbidity was 1.5% [95% confidence interval (CI), 1.5-1.5], and varied by a factor of 8.3 between states. Among those aged at least 50 years, 4.5% (95% CI, 4.3-4.7) with a BMI less than 23.0kg/m and 16.1% (95% CI, 15.0-17.4) with a BMI at least 30kg/m were comorbid. Age, BMI, household wealth quintile, male sex, and urban location were all positively associated with this comorbidity. CONCLUSION: A substantial proportion of India's population had both a raised blood glucose and BP, calling for integrated interventions to reduce cardiovascular disease risk. We identified large variation among states, age groups, and by rural-urban residency, which can inform health system planning and the targeting of interventions, such as appropriate screening programs, to those most in need.